2019
DOI: 10.5194/amt-12-3541-2019
|View full text |Cite
|
Sign up to set email alerts
|

Method to measure the size-resolved real part of aerosol refractive index using differential mobility analyzer in tandem with single-particle soot photometer

Abstract: Knowledge on the refractive index of ambient aerosols can help reduce the uncertainties in estimating aerosol radiative forcing. A new method is proposed to retrieve the size-resolved real part of the refractive index (RRI). The main principle of deriving the RRI is measuring the scattering intensity by a single-particle soot photometer (SP2) of size-selected aerosols. This method is validated by a series of calibration experiments using the components of the known RRI. The retrieved size-resolved RRI covers a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 46 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…The size-resolved BC core distribution and non-BC coating thickness were measured using a differential mobility analyzer (DMA, model 3081, TSI, USA) in tandem with a single-particle soot photometer (SP2, Droplet Measurement Technologies, USA). For detailed information on the DMA, the reader is referred to Zhao et al (2019c). SP2 can measure the BC mass concentration from the incandescence signals emitted by the BC particle, which is heated to around 6000 K by a laser with a wavelength of 1064 nm (Zhao et al, 2020b).…”
Section: Field Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The size-resolved BC core distribution and non-BC coating thickness were measured using a differential mobility analyzer (DMA, model 3081, TSI, USA) in tandem with a single-particle soot photometer (SP2, Droplet Measurement Technologies, USA). For detailed information on the DMA, the reader is referred to Zhao et al (2019c). SP2 can measure the BC mass concentration from the incandescence signals emitted by the BC particle, which is heated to around 6000 K by a laser with a wavelength of 1064 nm (Zhao et al, 2020b).…”
Section: Field Measurementsmentioning
confidence: 99%
“…The coating materials are also critical in regulating the morphology and optical properties as the coating of sulfuric acid has been shown to be more efficient in altering the BC morphology and light absorption (Zhang et al, 2008;Xue et al, 2009b, a). Zhao et al (2019b) reported that the light absorption properties of ambient BC particles are influenced by BC mass size distribution. In addition, recently, researchers have found that the E abs values are also controlled by particle-to-particle heterogeneity (Fierce et al, 2016(Fierce et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…The range of the measured RRI (1.34-1.56) is a little wider than the literature values. Past measurements of ambient aerosol RRI values vary between 1.4 and 1.6 (Dubovik, 2002;Guyon et al, 2003;Zhang et al, 2016) over a different measurement site. This is the first time that such high variations in ambient aerosol RRI have been observed at one site.…”
Section: Measurement Resultsmentioning
confidence: 99%
“…The refractive index of the core adopted here is 1.67+0.67i, which is the calculated mean value by comparing the measured light absorption and calculated light absorption properties (Zhao et al, 2020a). The refractive index of the shell is chosen to be 1.46+0i, which is 100 assumed to be as that of the non-BC component measured by the DMA-SP2 system (Zhao et al,101 2019a; Zhao et al, 2019c). With the above information, the σ values at a given Dp and a given Dc .…”
Section: Calculating the Aerosol Absorption Coefficient For A Given Dmentioning
confidence: 99%